Penguatan Kapasitas Guru dan Orang Tua dalam Mendampingi Anak Berkebutuhan Khusus Melalui Konseling Islam Berbasis Inklusi - Muktiali, Saiful; Gina Asri Ruwaida; Sukron Makmun; Djoko Nugroho (LPPM STEBIS YPII, 2025)
This community service activity aims to improve the ability of teachers and parents in assisting children with special needs (ABK) through the Inclusion-Based Islamic Counseling approach. The background of this program is the lack of understanding, skills, and minimal social and emotional support in assisting ABK. The Islamic counseling approach that emphasizes the values ​​of compassion, patience, and tolerance is a solution to strengthen their role. The methods used include interviews, observations, and participatory training. The results showed an increase in understanding of the needs of ABK, both physically (70%), mentally (75%), emotionally (80%), and socially (85%). Islamic Counseling also helps teachers and parents overcome skill limitations and provides emotional support. In conclusion, Inclusion-Based Islamic Counseling plays an important role in creating an inclusive environment and supporting the development of ABK. This program is recommended to continue to be developed through ongoing training for teachers and parents.